2014
DOI: 10.3389/fmicb.2014.00307
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of fibrolytic and methanogenic rumen microorganisms during in situ incubation of switchgrass determined by 16S rRNA gene profiling

Abstract: The rumen microbial ecosystem is known for its biomass-degrading and methane-producing phenotype. Fermentation of recalcitrant plant material, comprised of a multitude of interwoven fibers, necessitates the synergistic activity of diverse microbial taxonomic groups that inhabit the anaerobic rumen ecosystem. Although interspecies hydrogen (H2) transfer, a process during which bacterially generated H2 is transferred to methanogenic Archaea, has obtained significant attention over the last decades, the temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 31 publications
5
63
3
Order By: Relevance
“…However, it has been shown that, rather than the number, it is the distribution of different archaea species that drives the formation of CH 4 in the rumen (Morgavi et al 2010;Abecia et al 2012). The distribution of rumen bacteria and archaea species can be rapidly adapted according to the dynamics of rumen microorganisms determined by gene profiling (Piao et al 2014). In the present study, the enteric CH 4 emission measurements (416 AE 49 g/day; mean AE s.d.)…”
Section: Methane Emission and N Excretionmentioning
confidence: 68%
“…However, it has been shown that, rather than the number, it is the distribution of different archaea species that drives the formation of CH 4 in the rumen (Morgavi et al 2010;Abecia et al 2012). The distribution of rumen bacteria and archaea species can be rapidly adapted according to the dynamics of rumen microorganisms determined by gene profiling (Piao et al 2014). In the present study, the enteric CH 4 emission measurements (416 AE 49 g/day; mean AE s.d.)…”
Section: Methane Emission and N Excretionmentioning
confidence: 68%
“…In addition, from their in sacco data with switchgrass, Piao et al . () have suggested that early fermentation of soluble carbohydrates was likely to increase the H 2 partial pressure that may affect the activity of fibrolytic organisms. Moreover, the formation of multispecies consortia between fibrolytic and nonfibrolytic species may enhance degradation later in time (Shinkai et al .…”
Section: Discussionmentioning
confidence: 99%
“…Koike et al (2003) have suggested that it could be due to consumption of soluble carbohydrates by fibrolytic bacteria at the earliest phases of incubation, which could facilitate their growth, rather than rapid production of fibrolytic enzymes necessary for NDF digestion. In addition, from their in sacco data with switchgrass, Piao et al (2014) have suggested that early fermentation of soluble carbohydrates was likely to increase the H 2 partial pressure that may affect the activity of fibrolytic organisms. Moreover, the formation of multispecies consortia between fibrolytic and nonfibrolytic species may enhance degradation later in time (Shinkai et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria preferentially attach to damaged sites on the plant surface, whereas fungi are able to physically disrupt the ingested material via rhizoidal growth. Microbial attachment is absolutely essential for the development of the complex microbial populations required for feed digestion in the rumen and occurs via a multistep process: (1) displacement of the epiphytic microbiome by rumen microbes (time <1 h), (2) establishment of a primary colonizing community of generalist microbes that primarily metabolize accessible carbohydrates (time 1 h to 4 h), (3) loss of some primary colonizers and selection of secondary colonizers specialized in digesting hemicellulose and cellulose (time > 4 h; Figure 2) (Piao et al, 2014;Huws et al, 2016;Mayorga et al, 2016). Within this community are taxa including Butyrivibrio, Fibrobacter, Olsenella and Prevotella that do not change significantly in abundance during primary and secondary colonization Liu et al, 2016).…”
Section: Colonization Of Feed In the Rumenmentioning
confidence: 99%